Kajian Pemanfaatan Potensi Sungai Siduk Sebagai Sumber Air Baku Kota Ketapang Propinsi Kalimantan Barat - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
Abstract: Ketapang city like another cities in Province of West Kalimantan, in dry season has a problem of a water quality